2024
DOI: 10.3390/agronomy14020378
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Alternate Wetting and Drying and the System of Rice Intensification on Greenhouse Gas Emissions: A Review of Rice Cultivation Practices

James Dahlgreen,
Adam Parr

Abstract: Rice provides ~20% of human dietary energy and, for many people, a similar share of their protein. Rice cultivation, however, produces significant greenhouse gas (GHG) emissions, comparable to those from the aviation sector. The main GHG from rice production is methane, mostly a result of conventional rice cultivation (CRC) keeping rice fields continuously flooded during the crop cycle. There is extensive evidence that alternate wetting and drying (AWD) of rice fields substantially reduces methane emissions. A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Farmers in developing countries obtain consistently high yield ratios when they use intensive agroecological techniques (Badgley et al 2007, 92). These methods can also reduce GHG emissions (Burney et al 2010, 12052, Dahlgreen andParr 2024) and increase carbon sequestration (Das et al 2023).…”
Section: Greenwashingmentioning
confidence: 99%
“…Farmers in developing countries obtain consistently high yield ratios when they use intensive agroecological techniques (Badgley et al 2007, 92). These methods can also reduce GHG emissions (Burney et al 2010, 12052, Dahlgreen andParr 2024) and increase carbon sequestration (Das et al 2023).…”
Section: Greenwashingmentioning
confidence: 99%
“…• Climate change: This article reviews all of the studies found in the published literature that assess how much the emission of greenhouse gases from rice paddies is reduced by alternate-wetting-and-drying irrigation (AWD) and/or by SRI crop management, which includes AWD [27]. This effect is particularly important for reducing the generation of methane (CH 4 ), the greenhouse gas that contributes most quickly and most potently to global warming.…”
mentioning
confidence: 99%